Climate Change Impacts On Deep-Sea Benthic Assemblages In The Atlantic Ocean - Gaurisas, Daniela Yepes (2024)
The deep ocean is the largest and least known ecosystem on Earth, occupying more than 70% of the planet's surface and supporting almost the highest biodiversity on the planet, with unique diversity hotspots, but still, many of these areas have not even been mapped. Deep-sea marine ecosystems are particularly important in regulating the climate and the cycling of matter and energy on Earth. However, human activities such as fishing, oil and gas exploitation, and mining have intensified in recent decades, impacting deep benthic ecosystems and decreasing the important benefits they provide. Recent data indicates that the Atlantic Ocean is already experiencing significant abiotic changes and will continue to be impacted by global climate changes in the coming decades, expected to be more severe in tropical zones and faster in deeper ocean layers. Given that all these stressors can significantly alter deep-sea biodiversity and ecosystem functioning, deepening the knowledge of ecological processes in Atlantic deep benthic ecosystems is imperative. In this sense, this thesis has advanced in three main topics 1) clarifying benthic biogeographic patterns on the deep Brazilian margin, Western Atlantic; 2) experimentally assessing the role of the macrofauna in an abyssal ecosystem functioning in the NE Tropical Atlantic; and 3) experimentally evaluating the effects of future climate change stressors on a bathyal macrofaunal community in the NE Tropical Atlantic and elucidating the potential impacts of these stressors on benthic ecosystem functioning. Therefore, the first chapter provides a brief introduction to the theme of the thesis and its subsequent chapters, highlighting the importance of knowing the biodiversity, distribution, and the role of benthic organisms in the cycling of elements and nutrients on the seafloor. The second chapter analyses the composition and distribution of the benthos along the Brazilian deep continental margin and proposes the first biogeographical scheme for the Brazilian deep-sea based on latitudinal and temperature boundaries. The third chapter studies the characterization of a macrofaunal community in the abyssal NE Tropical Atlantic and, for the first time, assesses ecosystem functioning with a focus on the macrofauna role on organic matter cycling. The fourth chapter corresponds to the first ex-situ multi-stressor experiment evaluating the synergistic effects of climate change on a macrofaunal assemblage in the deep Atlantic. This thesis progressively reveals the importance of these approaches for understanding the functioning of deep-sea ecosystems in the Atlantic as a whole, and, therefore, indicates possible responses to climate changes expected for the next century.